Doctors during the COVID-19 pandemic: what are their duties and what is owed to them?. Issue 1 (15th October 2020) - Johnson, Stephanie B; Butcher, Frances
Abstract : Doctors form an essential part of an effective response to the COVID-19 pandemic. We argue they have a duty to participate in pandemic response due to their special skills, but these skills vary between different doctors, and their duties are constrained by other competing rights. We conclude that while doctors should be encouraged to meet the demand for medical aid in the pandemic, those who make the sacrifices and increased efforts are owed reciprocal obligations in return. When reciprocal obligations are not met, doctors are further justified in opting out of specific tasks, as long as this is proportionate to the unmet obligation.